Development of methanogens within cathodic biofilm in the single-chamber microbial electrolysis cell. (February 2019) - Li, Xiao; Zeng, Cuiping; Lu, Yaobin; Liu, Guangli; Luo, Haiping; Zhang, Renduo
Graphical abstract: Highlights: Rapid development of methanogens inhibited hydrogen production. The stratification of Methanobacteriaceae within the cathodic biofilm was observed. The methane production rate could be related to the mcrA gene copy numbers. Abstract: The aim of this study was to investigate the development of cathodic biofilm and its effect on methane production in a single-chamber microbial electrolysis cell (MEC). The MEC with 1 g/L acetate was successfully operated within 31 cycles (∼2400 h). The maximum methane production rate and average current capture efficiency in the MEC reached 93 L/m 3 ·d and 82%, respectively. Distinct stratification of Methanobacteriaceae within cathodic biofilm was observed after 9 cycles of operation. The relative abundance of Methanobacteriaceae in the microbial community increased from 45.3% (0–15 μm), 57.6% (15–30 μm), 66.9% (30–45 μm) to 77.2% (45–60 μm) within the cathodic biofilm. The methane production rates were positively correlated with the mcrA gene copy numbers in the cathodic biofilm. Our results should be useful to understand the mechanism of methane and hydrogen production in the MEC.